Delayed Type Allergic Itch-Associated Response Induced by Toluene-2,4-diisocyanate in Hairless Mice - Kazuhiro Fuchibe; Takeshi Nabe; Masanori Fujii; Nobuaki Mizutani; Kiichiro Danno; Akihide Koda; Shigekatsu Kohno (Elsevier, 2003)
ABSTRACT: To develop an allergic dermatitis model showing persistent scratching in mice, toluene-2,4-diisocyanate (TDI) was repeatedly painted onto the skin of hairless HR-1 mice, and induction of itch-associated scratching behavior was observed. When HR-1 mice were epicutaneously sensitized with 1% TDI and then challenged by repeated painting the cervicodorsal skin with 0.1% TDI once every 10 days until the 10th challenge, delayed type scratching responses peaked at 1 - 2 days after challenge. TDI at 0.1% hardly induced scratching in non-sensitized HR-1 mice. The delayed scratching response was influenced by neither an H1 nor 5-HT1/2 receptor antagonist. On the other hand, intradermal injection of histamine and serotonin induced frequent scratching in HR-1 mice. In conclusion, repeated application of TDI can induce delayed type allergic scratching. Although HR-1 mice are high responders to both histamine and serotonin, induction of the delayed response depends on neither of these chemical mediators. This delayed response may be useful in analyzing the mechanisms of allergic pruritis.